Study to enhance cementation of impurities from zinc leach liquor by modifying the shape and size of zinc dust - Rao M.D.; Meshram A.; Verma H.R.; Singh K.K.; Mankhand T.R. (My University, 2025)
Cementation is a prominent purification technique used for removal of copper, cadmium, cobalt, and nickel from impure zinc sulphate solution obtained after leaching of zinc ore. Zinc dust is primarily used for this purpose still the extent of purification is limited. The present study represents the encouraging result in context to utilization of zinc dust for better purification by altering its dosage, size and morphology. The investigations showed that 300% excess zinc dust dosage than stoichiometric results in enhanced cement formation. The study also revealed that fine size and ball milling of zinc dust favors cementation. Zinc dust of −300 mesh (BSS) after 2 h ball milling highly purifies the impure solution within 2 h contact time. The yield of the impurities removal after the optimized cementation is 100, 99.99, 100 and 15% for Cu, Cd, Ni and Co respectively. The kinetics of cementation has been also studied and revealed that the reaction is in mixed controlled mechanism for copper and cadmium cementation. At the same time, for nickel, it is considered to be chemically controlled. The activation energy for the cementation of copper, cadmium and nickel were 38.19, 30.87 and 68.15 kJ /mol, respectively. The estimated activation energies were found within the range which corroborates with the mixed and reaction model and ensures industrial feasibility of the proposed process. © 2020 Elsevier B.V.